A Lean Management Framework for Achieving Sustainability Through Reducing Risks During the Design Process - Ezzat Othman, Ayman Ahmed; Abdelrahim, Sherouk Mohamed (International Journal of Sustainable Construction Engineering and Technology, 2024)
The building sector is a substantial global industry that plays a significant role in the social and economic advancement of nations. The construction industry has been criticized for its unsustainable practices, including waste generation, pollution, and the consumption of non-renewable resources and energy. Duo the dynamic nature of the construction industry and the involvement of multiple parties with diverse goals, knowledge, and skills, the industry is susceptible to various risks that can undermine the sustainability of projects. This research aims to develop a Lean Management (LM) framework to deliver sustainable construction projects through reducing risks during the design process. A research methodology consisting of literature review, case studies and survey questionnaire was designed to achieve the research aim. Firstly, literature review was used to investigate the concepts of sustainability, risks in the design process and LM. Secondly, two case studies were presented and analysed to investigate the role of LM in achieving sustainability in construction projects through reducing the risks of the design process. Thirdly, a survey questionnaire was conducted with a representative sample of Architecture Design Firms (ADFs) in Egypt to investigate their perception and application of LM towards delivering sustainable projects by reducing the risks during the design process. A framework is developed to facilitate integrating LM within the design process to reduce risks during the design process as an approach for achieving sustainability goals. The research identifies 18 design risk factors, their causes and impacts on delivering sustainable project. In addition, it correlated LM tools and techniques that could be used to reduce risks during the design process. Case studies showed that ADFs that adopted LM approach succeeded in achieving sustainability objectives and reducing associated risks. Moreover, data analysis of the survey questionnaire helped ranking the presented risks by the ADFs along with investigating their perception towards using LM within the design process. These findings necessitated acting towards developing a framework to reduce these risks towards achieving sustainability objectives in construction projects.